CHANGES IN BLOOD GLUCOSE AND LIPID PROFILE DURING RAMADAN FASTING - Rehman, Jamil -ur-; Shafiq, Mohammad (Journal of Ayub Medical College Abbottabad, 2000)
Background: It is an established fact that fasting influences carbohydrate and lipid metabolism resulting in changes in blood levels of glucose and lipid profile. This study describes the changes observed in the volunteers who fasted throughout the month of Ramadan. Methods: After screening. 24 volunteers were included in the study on the basis of their fasting blood glucose and cholesterol levels and different tests were conducted on serum. Results: Blood glucose, cholesterol. TAG and LDL-C levels decreased significantly, while HDL-C level rose considerably at the end of month. But the blood chemistry picture almost returned back to the pre-Ramadan level once fasting was discontinued for two weeks. Conclusion: It can therefore, be interpreted that the beneficial changes observed during the month of Ramadan are transient and could only be maintained if the dietary habits of Ramadan are continued afterwards.